Atypical Clinical Manifestations of Loiasis and Their Relevance for Endemic Populations. (1st November 2019) - Buell, Kevin G; Whittaker, Charles; Chesnais, Cédric B; Jewell, Paul D; Pion, Sébastien D S; Walker, Martin; Basáñez, Maria-Gloria; Boussinesq, Michel
Abstract: Background: Loiasis is mostly considered a relatively benign infection when compared with other filarial and parasitic diseases, with Calabar swellings and eyeworm being the most common signs. Yet, there are numerous reports in the literature of more serious sequelae. Establishing the relationship between infection and disease is a crucial first step toward estimating the burden of loiasis. Methods: We conducted a systematic review of case reports containing 329 individuals and detailing clinical manifestations of loiasis with a focus on nonclassical, atypical presentations. Results: Results indicate a high proportion (47%) of atypical presentations in the case reports identified, encompassing a wide range of cardiac, respiratory, gastrointestinal, renal, neurological, ophthalmological, and dermatological pathologies. Individuals with high microfilarial densities and residing in an endemic country were at greater risk of suffering from atypical manifestations. Conclusions: Our findings have important implications for understanding the clinical spectrum of conditions associated with Loa loa infection, which extends well beyond the classical eyeworm and Calabar swellings. As case reports may overestimate the true rate of atypical manifestations in endemic populations, large-scale, longitudinal clinico-epidemiological studies will be required to refine our estimates and demonstrate causality between loiasis and the breadth of clinical manifestations reported. Even if the rates of atypical presentations were found to be lower, given that residents of loiasis-endemic areas are both numerous and the group most at risk of severe atypical manifestations, our conclusions support the recognition of loiasis as a significant public health burden across Central Africa. Abstract : Our (largest-to-date) systematic review on loiasis case reports assessed atypical clinical manifestations, that is, those not simply involving Calabar swellings or eyeworm passage. Forty-seven percent (154/329) of patients presented atypically, mostly involving vital organs. High microfilaremia was identified as a risk factor.